No there there : race, class, and political community in Oakland - Rhomberg, Chris, 1959- (University of California Press, 2004)
Taking Oakland as a case study of urban politics and society in the United States, Chris Rhomberg examines the city's successive episodes of popular insurgency for what they can tell us about critical discontinuities in the American experience of urban political community.